Geolinguistic studies in Brazil in five phases: From the Viscount of Pedra Branca to the atlases of traditional communities’ speech - de Sá, Edmilson José (International Journal of Humanities and Education Development (IJHED), 2020)
Considering the expansion of Dialectology in Brazil, which, in the 19th century, presented the first clues with the Viscount of Pedra Branca’s publication about the Brazilian Portuguese language compared to the European Portuguese spoken in Portugal, this paper presents the stages of development of the studies carried out since then and lists not only the periods that preceded Brazilian Geolinguistics, but the research that culminated with the publication of States Linguistic Atlases, the publication of the Linguistic Atlas of Brazil in 2014, idealized fifty years before, and the presentation of other documents already completed or designed, thus contemplating the entire Brazil length and completing the fourth phase of Geolinguistic studies. Twelve atlases were published in this phase, whose pioneering role was for Bahia speech, in 1963, and advanced in the work related to Minas Gerais (1977), Paraíba (1977). 1984), Sergipe (1987 and 2002), Paraná (1994), The Southern Region (2002), Pará (2004), Ceará (2009), Goiás (2015), Pernambuco (2016) and Amapá (2017). However, in recent years, researches of linguistic varieties in traditional communities, such as Indigenous, Fishermen and Quilombolas, as are named the descendants and remaining of communities formed by enslaved fugitives, has drawn the attention of researchers and the elaboration of linguistic atlases involving these culturally differentiated people speeches already signals the fifth phase of Geolinguistic studies in the country. Thus, it is intended to present a description of the works, their methodological constitution and a brief overview of the products of these works, which cataloged, at the time of their conclusion, presented specific linguistic marks of the speech of each state and informants’ profiles that allowed the verification of sociocultural interferences.